Morus ad Craneveldium literae Balduinianae novae - Schulte Herbr (Supplementa Humanistica Lovaniensia, 1997)
The collection of original humanist letters to Frans van Cranevelt, discovered and acquired for K.U.Leuven in 1989, covers the years between 1520 and 1523, thus preceding the two collections edited by De Vocht in 1928. The new letters are litterae amicales too, written by Cranevelt